World Summit on the Information Society and its legacy for global governance - Raboy, Marc (2004)
Highlights a range of questions about issues and process that chararacterize communication governance at the start of the 21st century. Indicates a new paradigm for global governance generally, in which information and communication issues are central, and in which new actors, particularly global civil society, will have to be involved.